Rancang Bangun Sistem Catu Daya dengan Metode Switching Mode Power Supply (SMPS) Berbasis Arduino untuk Aplikasi Electrospinner - Khoirul Effendi; Junaidi Junaidi; Sri Wahyu Suciyati (Jurnal Teori dan Aplikasi Fisika, 2020)
Research about power supplies has been developed for various requirement. The power supply is used to supply electronic devices and laboratory-scale equipment, one of which is electrospinner. Electrospinner is an instrument used to make nanofibers consisting of several components, namely: power supply, high voltage, syringe pump, and collector drum. Electrospinner requires a stable supply of voltage so that the system can work well and requires a lot of voltage supply to supply components from the electrospinner. Arduino-based switching mode power supply (SMPS) is designed in this research. Arduino-based SMPS makes it possible to produce a stable supply with many outputs. Arduino as a PWM generator is used to control the power supply output voltage based on duty cycle. The results of the study addressed the duty cycle affecting the output of the power supply. The output voltage generated by the power supply can be set from 0-100 V with an accuracy of 98.19%, an error of 1.81% and a precision of 0.02% which is stated by the variation of the coefficient. The power supply produced also has an extra output voltage of 15 VCT and 15 V.